2020
DOI: 10.3389/fcell.2020.591141
|View full text |Cite
|
Sign up to set email alerts
|

Rac and Arp2/3-Nucleated Actin Networks Antagonize Rho During Mitotic and Meiotic Cleavages

Abstract: In motile cells, the activities of the different Rho family GTPases are spatially segregated within the cell, and during cytokinesis there is evidence that this may also be the case. But while Rho’s role as the central organizer for contractile ring assembly is well established, the role of Rac and the branched actin networks it promotes is less well understood. To characterize the contributions of these proteins during cytokinesis, we manipulated Rac and Arp2/3 activity during mitosis and meiosis in sea urchi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
15
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(15 citation statements)
references
References 71 publications
0
15
0
Order By: Relevance
“…, 2019 ; Huang et al. , 2019 ; Pal et al. , 2020 ), but this is the first demonstration that Arp2/3 is linked to the control of intracellular pressure through NMII.…”
Section: Discussionmentioning
confidence: 79%
“…, 2019 ; Huang et al. , 2019 ; Pal et al. , 2020 ), but this is the first demonstration that Arp2/3 is linked to the control of intracellular pressure through NMII.…”
Section: Discussionmentioning
confidence: 79%
“…Alternatively, it is possible that this mutually exclusive pattern is a consequence of different wave regulators -e.g., different GTPases, Factin assembly factors, or F-actin binding proteins -that could be active in the waves outside of the contractile ring and excluded from within the contractile ring or vice versa. Consistent with this possibility, Arp2/3 networks have been proposed to antagonize Rho signaling during cytokinesis (Pal et al, 2020), and inactivation of Rac at the cleavage plane by the centralspindlin complex is necessary for normal cytokinesis (Canman et al, 2008;Bastos et al, 2012;Zhuravlev et al, 2017), making the segregation of these players a prerequisite for a succsful cytokinesis.…”
Section: Discussionmentioning
confidence: 92%
“…Rho GTPases are known to regulate actin dynamics ( Ridley, 2006 ). In motile cells, during the process of mitosis, the activities of GTPases of different Rho families are separated in intracellular space ( Pal et al, 2020 ). A previous study found that RhoD could stimulate actin polymerization and affect plasma membrane protrusion and/or vesicular traffic ( Ridley, 2006 ).…”
Section: Discussionmentioning
confidence: 99%
“…A previous study found that RhoD could stimulate actin polymerization and affect plasma membrane protrusion and/or vesicular traffic ( Ridley, 2006 ). Pal et al (2020) reported that manipulating Rac and Arp2/3 activity resulted in polar body defects during mitosis and meiosis in sea urchin embryos and sea star oocytes, and suggested that Rac and Arp2/3-mediated actin networks might directly antagonize Rho signaling. PAK is an effector downstream target of Rho-GTPases Rac1 and Cdc42, which can activate its downstream target cofilin via LIM kinase-1, and subsequently supports cell migration and invasion through the polymerization of actin filaments ( Mierke et al, 2020 ).…”
Section: Discussionmentioning
confidence: 99%